A Sufistic Analysis of Hasan's Spiritual Journey in the Novel Atheist - Bahtiar, Ahmad; Wirawan, Gunta; Raihana , Najwa; Hudaa, Syihaabul; Jabal An Nur, Muhammad (Universitas Ahmad Dahlan, 2025)
Atheis is a novel by Achdiat K. Mihardja published by Balai Pustaka in 1949. There are many studies on this novel. This proves that the novel Atheis is interesting and important to study. This research is a qualitative research using Sigmund Freud's psychoanalysis approach which emphasizes the important role of the unconscious mind in shaping human behavior and experience. The main elements in this theory are motivation, emotion and other aspects of personality. The results show that the novel Atheis contains many religious elements, especially in terms of Sufiistic aspects. In the novel Atheis, the main character, Hasan, experiences an inner debate when he meets his friend, Rusli, who adheres to the ideology of Marxism. As a result, he experiences an inner war between Marxism and Islam. on the other hand, it is depicted that the main character has a strong commitment to religion. Religious commitment is depicted in the story which includes various aspects, ranging from aspects of belief, aspects of practice, aspects of knowledge, aspects of experience, and aspects of consequences. Based on the five aspects, the knowledge aspect is the aspect that appears most often because it is owned and mastered by the characters.